Environmental factors controlling the phytoplankton blooms at the Patagonia shelf-break in spring - Garcia, Virginia M. T. (2008)
The shelf-break front formed between Argentinean shelf waters and the Malvinas Current flow shows a conspicuous band of high phytoplankton biomass throughout spring and summer, detected by ocean color sensors. That area is the feeding and spawning ground of several commercial species of fish and squid and is thought to play an important role in CO2 sequestration by the ocean. Phytoplankton blooms in this area have been mainly attributed to coccolithophorids, a group of calcite producing phytoplankton. Here we present the environmental factors associated with the spring bloom in the Patagonian shelf-break (40o - 48oS) in the austral spring 2004. A remarkable bloom of diatoms and dinoflagellates (approx. 1200 Km long) was observed along the front, where integrated chlorophyll values ranged from 90.3 to 1074 mg m-2. It is suggested that supply of macro-nutrients by upwelling and probably iron by both upwelling and shelf transport contribute to maintaining the spring bloom. Strong water column stability along the front allowed the accumulation of algal cells mainly in the top 50 m and their maintenance in the euphotic layer. East of the shelf-break front, macro nutrient levels were high (surface nitrate= 16.6 μM, phosphate=0.35 μM, silicate=4.0 μM), associated with low phytoplankton biomass (<2 mg m-3). This was due to mixing and advection associated with the Malvinas Current (MC) flow and to grazing pressure at a transitional site between the MC and the high chlorophyll patch. Primary production rates (determined by the 14C technique) ranged between 1.9 and 7.8 gC m-2 d-1. Primary production was highest near 42o S partly due to theelevated phytoplankton biomass, which consumed most nitrate and phosphate in surface waters in this region. These high primary production rates are comparable with maxima seasonal productivity at Eastern Boundary Currents. The large bloom extent in the Patagonian shelf-break (approximately 55,000 Km2 of >2 mg m-3 chlorophyll patch), the associated primary production rates and diatoms dominance indicate a potentially significant biological control of gases such as O2 and CO2 in surface layers. The main factors favoring the development and maintenance of these blooms are nutrient supply from Malvinas Current upwelling and water column stability. Other processes such as mixing or grazing play an important role in biomass modulation in the region.